Human-Mediated Gene Flow Contributes to Metapopulation Genetic Structure of the Pathogenic Fungus Alternaria alternata from Potato - Meng, Jing-Wen; He, Dun-Chun; Zhu, Wen; Yang, Li-Na; Wu, E-Jiao; Xie, Jia-Hui; Shang, Li-Ping; Zhan, Jiasui (Frontiers in Plant Science, 2018)
Metapopulation structure generated by recurrent extinctions and recolonizations plays an important role in the evolution of species but is rarely considered in agricultural systems. In this study, generation and mechanism of metapopulation structure were investigated by microsatellite assaying 725 isolates of Alternaria alternata sampled from potato hosts at 16 locations across China. We found a single major cluster, no isolate-geography associations and no bottlenecks in the A. alternata isolates, suggesting a metapopulation genetic structure of the pathogen. We also found weak isolation-by-distance, lower among than within cropping region population differentiation, concordant moving directions of potato products and net gene flow and the highest gene diversity in the region with the most potato imports. These results indicate that in addition to natural dispersal, human-mediated gene flow also contributes to the generation and dynamics of the metapopulation genetic structure of A. alternata in China. Metapopulation structure increases the adaptive capacity of the plant pathogen as a result of enhanced genetic variation and reduced population fragmentation. Consequently, rigid quarantine regulations may be required to reduce population connectivity and the evolutionary potential of A. alternata and other pathogens with a similar population dynamics for a sustainable plant disease management.